Three very simple games and what it takes to solve them - Ondřej Rydval; Andreas Ortmann; Michal Ostatnický (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
We study the nature of dominance violations in three minimalist dominance-solvable guessing games, featuring two or three players choosing among two or three strategies. We examine how subjects reported reasoning translates into their choices and beliefs about others choices, and how reasoning and choices relate to their measured cognitive and personality characteristics. Only about a third of our subjects reason in accord with dominance; they always make dominant choices and almost always expect others to do so. By contrast, around 60% of subjects describe reasoning processes inconsistent with dominance, yet a quarter of them actually make dominant choices and a fifth of them expect others to do so. Dominance violations seem to arise mainly due to subjects misrepresenting the strategic nature of the guessing games. Reasoning errors are more likely for subjects with lower ability to maintain and allocate attention, as measured by working memory, and for subjects with weaker intrinsic motivation and premeditation attitudes.
Keywords: C72; C92; D83; 330; cognition; bounded rationality; beliefs; guessing games; experiment; Nichtkooperatives Spiel; Beschränkte Rationalität; Test